Predicting the mechanical properties of semi-flexible pavement material with micromechanical modeling - Senlin Ling; Denis Jelagin; Manfred N. Partl; Daquan Sun; Hassan Fadil (Materials & Design, 2024)
Semi-flexible pavement (SFP) material is a composite comprising cement, coarse aggregates and asphalt mortar, which has complex mechanical properties. Traditional experimental methods struggle to accurately quantify the effect of each phase and their interfaces on the SFP's mechanical properties. Micromechanical modelling based on finite element method offers a promising solution. In this study, a new micromechanical model for SFP is proposed, idealizing the material by representative volume elements. SFP mesostructure is represented as a simplified five element composite consisting of cement, asphalt mortar, aggregate, pore and cement-asphalt mortar interface. Periodic boundary conditions are used to simulate an infinite repetitive structure within a finite computational domain. The resulting model allows evaluating the stiffness and damage resistance of SFP in a computationally efficient manner. This model is utilized to explore the mechanical properties of SFPs and the results are compared with the experimental findings. The results show that the model captures the uniaxial compressive strength and stiffness for all materials examined. The model is further used to evaluate the effect of properties of individual elements of SFP on its stiffness and strength. The feasibility of using the proposed modelling approach to optimize the material design of SFP is discussed.